2015
DOI: 10.1007/s10551-015-2838-3
|View full text |Cite
|
Sign up to set email alerts
|

Educating Business Students About Sustainability: A Bibliometric Review of Current Trends and Research Needs

Abstract: There has been substantial growth of interest in sustainability in business, management and organisational studies in recent years. This article applies Oswick's (J Manag Spirit Relig 6(1):15-25, 2009) method of bibliometric research to ascertain how this growth has been reflected in scholarly publishing, particularly as it relates to business and management education over the 20 years 1994-2013. The research has found that sustainability as a general topic in business and management studies, as evidenced by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 21 publications
0
47
0
2
Order By: Relevance
“…Bibliometrics consists of the "quantitative study of physical published units, or of bibliographic units, or of the surrogates of either" (Broadus, 1987, p. 376). Some recent bibliometric studies include: Teixeira, Iwamoto and Medeiros (2013), in the case of bibliometric studies in administration published in top Brazilian journals; Pinto, Serra and Ferreira (2014), on research into culture in international business; Sriwannawit and Sandström (2015), on diffusion research; Cullen (2015), on sustainability and business and management education; Oorschot, Hofman and Halman (2015), on innovation adoption; Lindahl, Stenling, Lindwall and Colliander (2015), on sports and exercise; and William, Tripp-Reimer, Daack-Hirsch and DeBerg (2016), on genomic nursing. A number of recent bibliometric studies have also been published in the leadership literature, such as Batistič, Černe and Vogel (2017) and Tal and Gordon (2016).…”
Section: Methodology Designmentioning
confidence: 99%
“…Bibliometrics consists of the "quantitative study of physical published units, or of bibliographic units, or of the surrogates of either" (Broadus, 1987, p. 376). Some recent bibliometric studies include: Teixeira, Iwamoto and Medeiros (2013), in the case of bibliometric studies in administration published in top Brazilian journals; Pinto, Serra and Ferreira (2014), on research into culture in international business; Sriwannawit and Sandström (2015), on diffusion research; Cullen (2015), on sustainability and business and management education; Oorschot, Hofman and Halman (2015), on innovation adoption; Lindahl, Stenling, Lindwall and Colliander (2015), on sports and exercise; and William, Tripp-Reimer, Daack-Hirsch and DeBerg (2016), on genomic nursing. A number of recent bibliometric studies have also been published in the leadership literature, such as Batistič, Černe and Vogel (2017) and Tal and Gordon (2016).…”
Section: Methodology Designmentioning
confidence: 99%
“…In general, the review suggests that the SMS knowledge base remains an emergent field of study that stills draws attention from diverse groups of international leading scholars in various fields, particularly in the three key areas of environmental science, strategic business management, and engineering. It is not limited to the traditional studies in green/ecological/environmental strategic management and sustainability since these studies are contributed to almost 64% of all documents [126]. In the recent times, the review found that the contemporary SMS knowledge was increasingly linked to business and management.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…Convém realçar que pesquisas suportadas por tecnologias emergentes têm o potencial de contribuir tanto em termos de métodos, ou mesmo como tema de pesquisa per se, versando acerca do impacto das tecnologias emergentes sobre os temas relevantes na pesquisa em negócios. É notória a evolução do volume de dados disponíveis e, por extensão, também é notória a carência de estudos caracterizados pelo exame de dados tão ricos quanto a oferta desses apresenta-se para o futuro próximo (Cullen, 2017;Iliho & Saritha, 2019). É possível que esta constatação seja decorrente da carência de pesquisadores detentores de habilidades que permitam a produção de conhecimento a partir de data driven research (Kimmons & Veletsianos, 2018).…”
unclassified